PLAY NICE BUT WIN : A CEO's Journey from Founder to Leader - Dell, Michael 1965- (New York : Portfolio / Penguin Random House, 2021)
"More than an honest portrait of a leader at a crossroads, Play Nice But Win is a survival story proving that while anyone with technological insight and entrepreneurial zeal might build something great-it takes a leader to build something that lasts"-- Provided by publisher
Keywords: Chief executive officers -- biography; Entrepreneurship; Leadership